ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MELALUI PENERAPAN BLENDED PROJECT BASED LEARNING - Candra, Riski Ayu; Prasetya, Agung Tri; Hartati, Ratni (Jurnal Inovasi Pendidikan Kimia, 2019)
The ability to express good ideas in a discussion and answer question can affect students' creative thinking abilities. The availability of wifi in schools is already very good, so blended learning based learning models can be applied to improve the learning process in schools. This study aims to determine the ability of students to think creatively in acid-base material using project-based learning combined with blended learning methods. The research method used is pre-experimental. The research design used is one-shot case study. This research was conducted with the stages of preparation, implementation, data retrieval, then analyzed, discussed, and concluded as a result of the research. The research subjects were taken by purposive sampling technique. The subjects in this study were students of class XI MIPA 3.4 of SMAN 1 Salatiga. Data collection techniques are carried out by testing creative thinking skills through essay or essay questions, observation sheets to measure the ability to think creatively and assessment of natural indicator projects. The average results of the percentage of creative thinking ability indicate that 67% of students are in a good category. The highest percentage for each indicator of creative thinking ability is detailed thinking skills (77%), fluency (72%), flexible thinking skills (65%) and original thinking skills (44%). The average rating percentage for making natural indicator projects is 83.3% with a very good category.